Synergistic yield of dual energy forms through biocatalyzed electrofermentation of waste: Stoichiometric analysis of electron and carbon distribution. (August 2015) - Nikhil, G.N.; Venkata Subhash, G.; Yeruva, Dileep Kumar; Venkata Mohan, S.
Abstract: A novel BEF (biocatalyzed electrofermentor) is designed by hybridizing the functional properties of both MFC (microbial fuel cell) and acidogenic fermentation process (AFP). This prototype facilitates potential synergy between the electrogenic and acidogenic processes to recover biohydrogen and bioelectricity with simultaneous wastewater treatment. The BEF was operated in three circuitry modes of operation viz., OC (open circuit), SC (short circuit) and CC (closed circuit) and the performance was compared with a control (without electrode assembly) with DSW (designed synthetic wastewater) having an organic load of 5000 mgL −1 . In comparison with other test conditions, CC mode with fixed external resistance (300 Ω) gave highest yields of power density (72 mW m − 2 ) and biohydrogen production (343 mL). Besides, the BEF performance was sustained by the innate buffering capacity and the substrate-linked dehydrogenase enzyme activity. The CC mode comparatively excelled because it facilitates congenial ambiance for the enriched EAB (electroactive bacteria) resulting high rate of metabolic activity that paves way for higher substrate degradation and product conversion efficiency. The empirical analysis of electron and carbon distribution was in good agreement with the experimental results. The electron delivery kinetics studied using voltammetric technique confirmed electron transfer by the membrane bound redox mediators. The designed biocatalyzed electrofermentation unravels the scope to harness dual forms of energy along with waste remediation. Graphical abstract: Highlights: Novel hybrid reactor for harnessing bioelectricity and biohydrogen simultaneously. System buffering was critical factor during acidogenic–electrogeneic processes. Electron-carbon balance revealed the rationale for substrate distribution. Closed circuitry operation was efficient for electron delivery supported by voltammograms.